5.8 Modeling with Quadratic Functions

Slides:



Advertisements
Similar presentations
Quadratic Functions.
Advertisements

Graphing Quadratic Functions
How do I write quadratic functions and models? 7.2 Write Quadratic Functions and Models Example 1 Write a quadratic function in vertex form Write a quadratic.
4.10: Write Quadratic Functions and Models HW: p.312 – 313 (4, 12, 18, 22, 28, 34) Test : Wednesday.
Adapted from Walch Education  The standard form of a quadratic function is f ( x ) = ax 2 + bx + c, where a is the coefficient of the quadratic term,
Essential Question: How do you determine whether a quadratic function has a maximum or minimum and how do you find it?
M.M. 10/1/08 What happens if we change the value of a and c ? y=3x 2 y=-3x 2 y=4x 2 +3 y=-4x 2 -2.
Write a quadratic function in vertex form
Graphing Quadratic Equations. What does a quadratic equation look like? One variable is squared No higher powers Standard Form y = ax 2 + bx + c y = x.
7.3 Multivariable Linear Systems.
3.2 Solving Systems Algebraically
Quadratic Functions. The graph of any quadratic function is called a parabola. Parabolas are shaped like cups, as shown in the graph below. If the coefficient.
The General Quadratic Function Students will be able to graph functions defined by the general quadratic equation.
1. 2 Any function of the form y = f (x) = ax 2 + bx + c where a  0 is called a Quadratic Function.
EXAMPLE 1 Write a quadratic function in vertex form Write a quadratic function for the parabola shown. SOLUTION Use vertex form because the vertex is given.
GraphingSubstitutionEliminationNon-LinearInequalities
Finding a Quadratic Equation from Three Coordinates.
Name: Date: Topic: Solving & Graphing Quadratic Functions/Equations Essential Question: How can you solve quadratic equations? Warm-Up : Factor 1. 49p.
Chapter 10 Review for Test. Section 10.1:Graph y = ax² + c Quadratic Equation (function) _____________ Parabola is the name of the graph for a quadratic.
Graphing Quadratic Equations
QUADTRATIC RELATIONS. A relation which must contain a term with x2 It may or may not have a term with x and a constant term (a term without x) It can.
Do Now (3x + y) – (2x + y) 4(2x + 3y) – (8x – y)
EXAMPLE 1 Solve an equation with two real solutions Solve x 2 + 3x = 2. x 2 + 3x = 2 Write original equation. x 2 + 3x – 2 = 0 Write in standard form.
Lesson: Objectives: 5.1 Solving Quadratic Equations - Graphing  DESCRIBE the Elements of the GRAPH of a Quadratic Equation  DETERMINE a Standard Approach.
EXAMPLE 4 Solve linear systems with many or no solutions Solve the linear system. a.x – 2y = 4 3x – 6y = 8 b.4x – 10y = 8 – 14x + 35y = – 28 SOLUTION a.
Big Idea: -Graph quadratic functions. -Demonstrate and explain the effect that changing a coefficient has on the graph. 5-2 Properties of Parabolas.
5-1 Graphing Quadratic Functions Algebra II CP. Vocabulary Quadratic function Quadratic term Linear term Constant term Parabola Axis of symmetry Vertex.
Section 3.1 Day 2 – Quadratic Functions After this section you should be able to: Graph a quadratic function with and without a calculator. Find the coordinates.
Chapter 4 Section 10. EXAMPLE 1 Write a quadratic function in vertex form Write a quadratic function for the parabola shown. SOLUTION Use vertex form.
Quadratic Functions PreCalculus 3-3. The graph of any quadratic function is called a parabola. Parabolas are shaped like cups, as shown in the graph below.
Write a quadratic function in vertex form
Graphing Quadratic Functions
Do Now Find the value of y when x = -1, 0, and 2. y = x2 + 3x – 2
Coefficients a, b, and c are coefficients Examples: Find a, b, and c.
5-2 Properties of Parabolas
Investigating Characteristics of Quadratic Functions
Lesson 1-7 `Quadratic Functions and their Graphs Object
Copyright 2013, 2010, 2007, 2005, Pearson, Education, Inc.
Algebra I Section 9.3 Graph Quadratic Functions
Graphing Quadratic Functions
Graphing Quadratic Functions
Solving Quadratic Equation and Graphing
Creating and Graphing Equations Using Vertex Form
ALGEBRA I : SECTION 9-1 (Quadratic Graphs and Their Properties)
Solving a Quadratic Equation by Graphing
Use back - substitution to solve the triangular system. {image}
Copyright © 2014, 2010, 2007 Pearson Education, Inc.
Lesson 7.1 How do you solve systems of linear equations by graphing?
3.1 Quadratic Functions and Models
GRAPHING QUADRATIC FUNCTIONS
4.10 Write Quadratic Functions and Models
Copyright © 2014, 2010, 2007 Pearson Education, Inc.
9.1 Graphing Quadratic Functions
Review: Simplify.
Graphs of Quadratic Functions Part 1
Characteristics of Quadratic Functions
Chapter 10 Final Exam Review
Copyright © 2014, 2010, 2007 Pearson Education, Inc.
3.1 Quadratic Functions and Models
Graphing Quadratic Functions
Linear and Quadratic Functions
Systems of Equations Solve by Graphing.
Section 10.2 “Graph y = ax² + bx + c”
Quadratic Functions Graphs
Writing Quadratic Functions in Intercept Form
Graphing Quadratic Equations
Write Quadratic Functions and Models
9-3 Graphing y = ax + bx + c up 1a. y = x - 1 for -3<x<3
Factorise and solve the following:
Quadratic Functions and Equations Lesson 1: Graphing Quadratic Functions.
Presentation transcript:

5.8 Modeling with Quadratic Functions

Modeling with Quadratic Functions   Depending on what information we are given will determine the form that is the most convenient to use.

Graphing y=x2 Standard Vertex y = ax2+bx+c y= a (x - h)2+k axis: axis: x = h vertex ( x , y ) vertex ( h , k ) C is y-intercept a>0 U shaped, Minimum a<0 ∩ shaped, Maximum

1. Write a quadratic function for the parabola shown. Use vertex form because the vertex is given. y = a(x – h)2 + k Vertex form y = a(x – 1)2 – 2 Substitute 1 for h and –2 for k. Use the other given point, (3, 2), to find a. 2 = a(3 – 1)2 – 2 Substitute 3 for x and 2 for y. 2 = 4a – 2 Simplify coefficient of a. 1 = a Solve for a. A quadratic function for the parabola is y = 1(x – 1)2 – 2.

Use vertex form because the vertex is given. y = a(x – h)2 + k 2. Write a quadratic function whose graph has the given characteristics. vertex: (4, –5) passes through: (2, –1) Use vertex form because the vertex is given. y = a(x – h)2 + k Vertex form y = a(x – 4)2 – 5 Substitute 4 for h and –5 for k. Use the other given point, (2,–1), to find a. –1 = a(2 – 4)2 – 5 Substitute 2 for x and –1 for y. –1 = 4a – 5 Simplify coefficient of x. 1 = a Solve for a. A quadratic function for the parabola is y = 1(x – 4)2 – 5. ANSWER

Use vertex form because the vertex is given. passes through: (0, –8) Use vertex form because the vertex is given. y = a(x – h)2 + k Vertex form y = a(x + 3)2 + 1 Substitute –3 for h and 1 for k. Use the other given point, (0,–8), to find a. –8 = a(0 + 3)2 + 1 Substitute 2 for x and –8 for y. –8 = 9a + 1 Simplify coefficient of x. –1 = a Solve for a. A quadratic function for the parabola is y = 1(x + 3)2 + 1. ANSWER

Steps for solving in 3 variables Using the 1st 2 equations, cancel one of the variables. Using the last 2 equations, cancel the same variable from step 1. Use the results of steps 1 & 2 to solve for the 2 remaining variables. Plug the results from step 3 into one of the original 3 equations and solve for the 3rd remaining variable. Write the quadratic equation in standard form.

4. Write a quadratic function in standard form for the parabola that passes through the points STEP 1 Substitute the coordinates of each point into y = ax2 + bx + c to obtain the system of three linear equations shown below. –3 = a(–1)2 + b(–1) + c Substitute –1 for x and -3 for y. –3 = a – b + c Equation 1 –4 = a(0)2 + b(0) + c Substitute 0 for x and – 4 for y. – 4 = c Equation 2 6 = a(2)2 + b(2) + c Substitute 2 for x and 6 for y. 6 = 4a + 2b + c Equation 3

STEP 2 Rewrite the system of three equations in Step 1 as a system of two equations by substituting – 4 for c in Equations 1 and 3. a – b + c = – 3 Equation 1 a – b – 4 = – 3 Substitute – 4 for c. a – b = 1 Revised Equation 1 4a + 2b + c = 6 Equation 3 4a + 2b - 4 = 6 Substitute – 4 for c. 4a + 2b = 10 Revised Equation 3

STEP 3 Solve the system consisting of revised Equations 1 and 3. Use the elimination method. a – b = 1 2a – 2b = 2 4a + 2b = 10 4a + 2b = 10 6a = 12 a = 2 So 2 – b = 1, which means b = 1. The solution is a = 2, b = 1, and c = – 4. A quadratic function for the parabola is y = 2x2 + x – 4. ANSWER

5. Write a quadratic function in standard form for the parabola that passes through the given points. (–1, 5), (0, –1), (2, 11) STEP 1 Substitute the coordinates of each point into y = ax2 + bx + c to obtain the system of three linear equations shown below. 5 = a(–1)2 + b(–1) + c Substitute –1 for x and 5 for y. 5 = a – b + c Equation 1 –1 = a(0)2 + b(0) + c Substitute 0 for x and – 1 for y. – 1 = c Equation 2 11 = a(2)2 + b(2) + c Substitute 2 for x and 11 for y. 11 = 4a + 2b + c Equation 3

STEP 2 Rewrite the system of three equations in Step 1 as a system of two equations by substituting – 1 for c in Equations 1 and 3. a – b + c = 5 Equation 1 a – b – 1 = 5 Substitute – 1 for c. a – b = 6 Revised Equation 1 4a + 2b + c = 11 Equation 3 4a + 2b – 1 = 11 Substitute – 1 for c. 4a + 2b = 12 Revised Equation 3

y = 4x2 – 2x – 1 STEP 3 Solve the system consisting of revised Equations 1 and 3. Use the elimination method. a – b = 6 2a – 2b = 12 4a + 2b = 10 4a + 2b = 12 6a = 24 a = 4 So, 4 – b = 6, which means b = – 2 A quadratic function for the parabola is 4x2 – 2x – 1 y = ANSWER

6. (1, 0), (2, -3), (3, -10) STEP 1 Substitute the coordinates of each point into y = ax2 + bx + c to obtain the system of three linear equations shown below. 0 = a(1)2 + b(1) + c Substitute 1 for x and 0 for y. 0= 1a + 1b + c Equation 1 -3 = a(2)2 + b(2) + c Substitute 2 for x and- 3 for y. -3 = 4a +2b + c Equation 2 -10 = a(3)2 + b(3) + c Substitute 3 for x and -10 for y. -10 = 9a + 3b + c Equation 3

STEP 2 PART 1 -1 0 = 1a + 1b + c 0 = -1a - 1b - c -3 = 4a +2b + c Rewrite the system of three equations in Step 1 as a system of two equations. Use Elimination to simplify one set of equations then use substitution & elimination to find the PART 1 -1 0 = 1a + 1b + c 0 = -1a - 1b - c Equation 1 -3 = 4a +2b + c -3 = 4a +2b + c Equation 2 -3 = 3a +1b PART 1 PART 2 -1 3 = -4a -2b - c -3 = 4a +2b + c Equation 2 -10 = 9a + 3b + c Equation 3 -10 = 9a + 3b + c -7 = 5a + 1b PART 2 -3 = 3a +1b -1 3 = -3a - 1b PART 1 -7 = 5a + 1b -7 = 5a + 1b PART 2 -4 = 2a -2 = a

STEP 3 Solve for the remaining variables by substitution. Original equations -3 = 3a +1b 0 = 1a + 1b + c PART 1 -3 = 4a +2b + c -7 = 5a + 1b PART 2 -10 = 9a + 3b + c -2 = a -3 = 3a +1b -3 = 3(-2) +1b -3 = -6 +1b 3 = b 0 = 1a + 1b + c 0 = 1(-2) + 1(3) + c 0 = -2 + 3 + c 0 = 1 + c -1 = c

y = -2x2 + 3x -1 Substitute y = ax2 + bx + c -2 = a 3 = b -1 = c FINAL ANSWER!!